A study to evaluate cardiovascular responses by using treadmill and ergometer bicycle exercise in young adults - Alok Kumar Yadav (Indian Journal of Health Sciences and Biomedical Research KLEU, 2018)
BACKGROUND AND OBJECTIVE: Exercise is inevitable to keep good health status, advised for health promotion, diagnosis of diseases, and rehabilitation. Different types of exercise are performed as exercise tolerance, but tolerance is not same for every individual. Thus, the objective of this study is to evaluate the cardiovascular responses for three different intensities of exercise using treadmill and bicycle ergometer at fixed heart rate (HR) value in young healthy adults. METHODS: After obtaining the ethical clearance from the Institutional Ethical Committee, a total of 130 participants were screened and 48 randomly selected male and female individuals with age group of 18–24 years and with normal body mass index. Selected participants are divided into three groups according to HR using WHO classification and Karvonen formula of exercise intensity. Sixteen individuals in each group start exercising for treadmill exercise at 3, 6, and 7.5 k/h, respectively, with zero inclination and for ergometer bicycle exercise at pedal frequency 50–60, 70–80, and 90–100 rpm, respectively, with 0 kg breaking resistance until calculated target HR is achieved. Cardiovascular parameters such as (systolic blood pressure [SBP], diastolic blood pressure [DBP], and rate pressure product [RPP]) pre- and post-exercise were recorded, and data are subjected to statistical analysis in both modes of exercise. RESULTS: SBP and RPP are linearly increased with increasing intensity of exercise and more observed in ergometer bicycling than treadmill exercise. Postexercise mean DBP among the three intensities of exercise: in mild exercise, there was negligible change in case of treadmill exercise and a higher mean DBP was recorded in case of ergometer bicycle exercise; in moderate exercise, value was slightly lower in treadmill exercise and slightly higher in ergometer bicycle exercise, but in severe exercise, mean DBP decreased in both treadmill as well as in ergometer bicycle exercise. CONCLUSION: Each mode of exercise has its own advantage and disadvantage depends on individual's physical condition and requirement.